Subcortical Brain Abnormalities and Clinical Relevance in Patients With Hemifacial Spasm - Xu, Hui; Guo, Chenguang; Luo, Feifei; Sotoodeh, Romina; Zhang, Ming; Wang, Yuan (Frontiers in Neurology, 2020)
Purpose: Hemifacial spasm (HFS), a rare neuromuscular movement disorder, is characterized by unilateral, irregular and paroxysmal facial muscle contractions. To elucidate the central neural mechanisms of HFS, we conducted vertex-wise shape analyses to investigate volume and shape alterations of subcortical structures, which could help to better understand the abnormality in distinct subcortical regions and determine alternative biomarkers of HFS. Methods: Thirty patients with HFS and 30 age- and sex-matched healthy controls provided written informed consent. T1-weighted structural magnetic resonance imaging (MRI) data were collected from all participants. Vertex-wise shape analyses were performed to assess the volume and shape alterations of subcortical structures following HFS. Post hoc correlations with spasm severity and measures of mood dysfunction were applied to characterize subcortical brain alterations. Results: Compared with healthy controls, patients with HFS showed increased volume specifically in the right caudate. Furthermore, patients exhibited significant shape atrophy in the anterior medial aspect of left pallidum, together with shape expansion in the anterior ventrolateral aspect of right caudate head. In addition, shape alteration in right caudate was positively correlated with both anxious and depressive symptoms in HFS patients. Conclusions: This is the first study to investigate subcortical brain abnormalities in patients with HFS. Our findings provide compelling evidence for subcortical brain alterations specific to HFS, and further may shed light on the pathophysiology of HFS and apply to the translational medicine.